Experiencing human resource management - Mabey, Christopher, 1951-; Skinner, Denise; Clark, Timothy, 1964- (Sage Publications, 1998)
By examining human resource management (HRM) techniques and processes from the r̀eceiving end', Experiencing Human Resource Management provides a rich and valuable view of HRM initiatives and strategies. If HRM is to contribute to the objectives of the organization, it is imperative to understand how HRM techniques are being applied and experienced. The current HRM literature is dominated by a managerial focus and perspective, however this book tells the experiences of employees in more than 20 organizations across a number of sectors and countries. It sets out to answer three questions: A dec.